Body percussion and imitation: pedagogical resources from the neuromotricity perspective (Per Musi, 2024)
Imitation in the teaching of music is a resource that comes from oral traditions, and that later western culture transformed with many variants through the canon or counterpoint among other musical forms. The BAPNE method has four ways of learning, where imitation is executed from another praxis very different from the classical one. The aim of this work is to provide, both theoretically and practically, another pedagogical model of imitation from the point of view of body percussion and neuromotricity. To this end, it will focus on other structures on a practical level called simple imitation, progressive imitation, inhibitory imitation, and divided imitation, with their verbal, kinaesthetic and mixed variants, which are a complete departure from classical learning models. These types of imitation are based on a model linked to motor skills for the development of cognitive function.